Development of an All-Wales National Health Service Surgical Lymphedema Supermicrosurgery Service - Ross Weale, MBBS, MRCS, BSc; Mia Thomas, MBBS; Cheryl Pike, DProf, MCSP; Melanie Thomas, MBE, DProf, FCSP; Zita M. Jessop, MA (Cantab), MB BChir, MRCS, PhD; Thomas Bragg, FRCS (Plast); Amar Ghattaura, MBBS, BSc, MSc, FRCS (Plast) (Plastic and Reconstructive Surgery, Global Open)
Background:. The management of lymphedema includes an array of conservative measures, but must also include surgical intervention as a management option where appropriate. Within the National Health Service in Great Britain, the surgical provision for lymphedema patients is very minimal. This article provides a historical overview of the inception of the lymphedema service within Wales, which is the only holistic lymphedema service within the National Health Service. Methods:. All patients discussed at the lymphedema multidisciplinary team (MDT) meeting were included. Data were collected during a 5-year period from June 2017 to May 2022. MDT meeting outcomes were also recorded (conservative or surgical management), and if surgical intervention was used, the type of surgical procedure was documented. Results:. A total of 175 patients were discussed by the lymphedema surgical MDT. Of these, 129 (74%) were recommended for surgery and 46 (26%) were managed using conservative measures alone. The most common surgical recommendation was for lymphovenous anastomosis (61, 47%), followed by liposuction (40, 31%). Vascularized lymph node transfer was recommended in 19 (15%) cases. Conclusions:. The authors highlight the efficiency of the service, whereby despite more than 7500 referrals a year, only a small minority that are eligible for surgery undergo a surgical assessment. The authors hope that this article provides an impetus for such services to be similarly replicated across other nations.